PENGALOKASIAN DANA DESA DI NAGARI SIMPANG KAPUAK KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT TAHUN 2023-2024 - Fajar, M. Alwi; Nisaa, Fadhiilatun (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the non-realization of the SDGs data validation and determination deliberation program, despite being budgeted in the 2023 Village Revenue and Expenditure Budget (APB Nagari). The purpose of this study is to describe the allocation of Village Funds in Nagari Simpang Kapuak in 2023-2024 and to identify the obstacles faced in its implementation. The analysis was conducted based on Nurhayati's (2017) effectiveness theory, which includes four indicators: achievement of objectives, timeliness, suitability of benefits, and results meeting expectations and targets. This research used a qualitative approach with a descriptive method. Data were collected through interviews, documentation, and literature studies. The results showed that the budget allocation in the sub-sector of village information development was ineffective. The planned activities were not implemented, thus the objectives were not achieved, the timing was not appropriate, the benefits were not felt by the community, and the program targets were not met. The main obstacles faced included a lack of understanding among officials, minimal technical assistance from the district and provincial governments, and no support from third parties. The budget allocation in the sub-sector of village information development in Nagari Simpang Kapuak in 2023 was deemed ineffective. Although the program was removed, overall there was a slight increase in the total income and expenditure of Nagari Simpang Kapuak from 2023 to 2024, and in 2024, no sub-fields were unrealized, indicating efforts to improve budget effectiveness. Keywords: Budget Effectiveness, Budget Allocation, Village Fund